Medical Error – Should it be a Criminal Offence? - Šepec, Miha (Medicine, Law & Society, 2018)
Medicine is a risky profession where medical professionals have a duty to do anything in their power to help their patients. However, what if a doctor makes a grievous mistake that leads to the death but could have been avoided? Are moral responsibility and apology to patients’ family enough? Should we impose sanctions (civil or criminal) on the doctor who negligently caused the patients’ death? To answer this questions, we present arguments against criminalisation of medical error, where the strongest arguments are uncertainty of medical standards, counterproductive criminalisation seen in defensive medicine, using criminal law as the last resort, and the argument of doctor’s immunity. On the other hand, arguments for criminalisation are obvious negligent treatment with serious consequences, general prevention of future negligent conduct, sanitation of a medical system gone wrong, and the argument of privileged criminal offence. Our conclusion is that criminal law repression of medical malpractice or medical error is justified, however only in the most obvious cases of undisputed negligence or carelessness of a doctor, where his inappropriate conduct has led to a serious deterioration of health of a patient, which could have easily been avoided, if a doctor respected the practice and rules of medical science and profession.